Gene editing for the efficient correction of a recurrent COL7A1 mutation in recessive dystrophic epidermolysis bullosa keratinocytes - Chamorro, Cristina; Haußer-Siller, Ingrid (Molecular therapy. Nucleic Acids, 2016)
Clonal gene therapy protocols based on the precise manipulation of epidermal stem cells require highly efficient gene-editing molecular tools. We have combined adeno-associated virus (AAV)-mediated delivery of donor template DNA with transcription activator-like nucleases (TALE) expressed by adenoviral vectors to address the correction of the c.6527insC mutation in the COL7A1 gene, causing recessive dystrophic epidermolysis bullosa in a high percentage of Spanish patients. After transduction with these viral vectors, high frequencies of homology-directed repair were found in clones of keratinocytes derived from a recessive dystrophic epidermolysis bullosa (RDEB) patient homozygous for the c.6527insC mutation. Gene-edited clones recovered the expression of the COL7A1 transcript and collagen VII protein at physiological levels. In addition, treatment of patient keratinocytes with TALE nucleases in the absence of a donor template DNA resulted in nonhomologous end joining (NHEJ)-mediated indel generation in the vicinity of the c.6527insC mutation site in a large proportion of keratinocyte clones. A subset of these indels restored the reading frame of COL7A1 and resulted in abundant, supraphysiological expression levels of mutant or truncated collagen VII protein. Keratinocyte clones corrected both by homology-directed repair (HDR) or NHEJ were used to regenerate skin displaying collagen VII in the dermo-epidermal junction.
Gesehen am 11.11.2019